2011
DOI: 10.1016/j.neuroimage.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cortical representations of the rodent forepaw and hindpaw with BOLD fMRI reveals two spatial boundaries

Abstract: Electrical stimulation of the rat forepaw and hindpaw was employed to study the spatial distribution of BOLD fMRI. Averaging of multiple fMRI sessions significantly improved the spatial stability of the BOLD signal and enabled quantitative determination of the boundaries of the BOLD fMRI maps. The averaged BOLD fMRI signal was distributed unevenly over the extent of the map and the data at the boundaries could be modeled with major and minor spatial components. Comparison of three-dimensional echo-planar imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 70 publications
5
10
0
Order By: Relevance
“…The difference between the two stimulation times was 5%, on average, over all 14 identified cells. These results are in agreement with previous reports showing that exposure to food stimuli soon elicits a state of food-induced arousal and food consumption, which can last tenths of minutes and is associated with an increase in the neuronal excitability in several ganglia, including the buccal ganglia (7,22). However, prolonged stimulation leads to a gradual decrease in these behavioral and neuronal responses as a result of satiation, sensory adaptation, and habituation (23-25).…”
Section: Significancesupporting
confidence: 93%
See 2 more Smart Citations
“…The difference between the two stimulation times was 5%, on average, over all 14 identified cells. These results are in agreement with previous reports showing that exposure to food stimuli soon elicits a state of food-induced arousal and food consumption, which can last tenths of minutes and is associated with an increase in the neuronal excitability in several ganglia, including the buccal ganglia (7,22). However, prolonged stimulation leads to a gradual decrease in these behavioral and neuronal responses as a result of satiation, sensory adaptation, and habituation (23-25).…”
Section: Significancesupporting
confidence: 93%
“…These data agreed well with the strong increase in the Mn 2+ concentration measured in the buccal ganglia coming from animals that were allowed to ingest food (STIM1 or STIM3). Moreover, the presence of food in the animal's surrounding environment, in contrast to its presence in the buccal cavity, stimulates the perioral zone (lips and rhinophores) and generates an appetitive behavior that does not require neuronal activity in the buccal ganglia (7,23). The stimuli from this perioral zone are conveyed by peripheral nerves to the cerebral ganglion, which triggers activity in neuronal networks that are primarily located in the pedal-pleural ganglia rather than the buccal ganglia.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiological studies of the infragranular layers have similarly shown larger responses to forepaw stimulation compared with hindpaw stimulation both with single-neuron recordings [48] and with local field potentials [51]. Moreover, studies employing intrinsic optical imaging [52] and BOLD fMRI [53] have also shown the same result. Larger responses to forepaw compared to hindpaw stimuli could therefore represent a general property of the rat somatosensory system.…”
Section: Discussionmentioning
confidence: 89%
“…In recent years, blood oxygenation level dependence functional MRI (BOLD-fMRI) has demonstrated its particular value in preoperative risk assessment in patients with LGG, which can facilitate planning of surgery, shorten the duration of the operation, and obtain prognostic information prior to surgery [3]. Nevertheless, BOLD-fMRI only provides information on cortical representation of brain function, but not on the course of the subcortical and deep white matter tracts [4,5]. As the white matter possesses about 50% of the adult brain volume and consists of a complex array of neuronal fiber connectivity [6], brain lesions often affect the white matter and may alter the known anatomical path in which the fiber pass.…”
Section: Introductionmentioning
confidence: 99%